2021
DOI: 10.1002/ams2.683
|View full text |Cite
|
Sign up to set email alerts
|

Simple prognostic factors and change of inflammatory markers in patients with severe coronavirus disease 2019: a single‐center observational study

Abstract: Aim The aim of this study was to investigate the prognostic factors and evaluate the change in inflammatory markers of patients with coronavirus disease 2019 (COVID‐19) requiring mechanical ventilation. Methods This retrospective observational study conducted from April 1, 2020, to February 18, 2021, included 97 adult patients who required mechanical ventilation for severe COVID‐19 pneumonia and excluded nonintubated patients with a positive COVID‐19 polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…All studies highlighted a possible relationship between PSP levels and COVID-19 severity, but this correlation was statistically significant in 10 works (1005 patients over 1373) [18,19,[22][23][24][27][28][29][30][31]. Among studies involving adult patients [17][18][19][20][21][22][23][24][25][27][28][29][30][31], the mean age of the pooled sample was 62.7 ± 5.7 years. Mortality in the included studies ranged between 8 and 45%.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies highlighted a possible relationship between PSP levels and COVID-19 severity, but this correlation was statistically significant in 10 works (1005 patients over 1373) [18,19,[22][23][24][27][28][29][30][31]. Among studies involving adult patients [17][18][19][20][21][22][23][24][25][27][28][29][30][31], the mean age of the pooled sample was 62.7 ± 5.7 years. Mortality in the included studies ranged between 8 and 45%.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Considering that sepsis and SARS-CoV-2 infection share immunopathogenetic and pathophysiological similarities, we believe that PSP may help in risk stratification [16]. In the last two years of pandemic, the interest in the possible correlation between COVID-19 severity and levels of PSP has increased and several studies have been published [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In 2021, Amhed et al proposed a review on this correlation [39] highlighting that PSP levels predicted the aggravation of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effectiveness of other steroids has been previously tested, 2,3 the optimal dose and duration of steroid therapy remains unclear 4–6 . In Japan, high‐dose steroids (e.g., methylprednisolone [mPSL] 1000 mg/day) are routinely used for treating interstitial pneumonia, whereas steroid pulse therapy (SPT) has been prescribed for critically‐ill COVID‐19 pneumonia patients 7–9 . Three randomized controlled trials (RCTs) showed that high‐dose steroid therapy improved outcomes in moderate to critically ill COVID‐19 pneumonia patients 4,5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In Japan, high-dose steroids (e.g., methylprednisolone [mPSL] 1000 mg/day) are routinely used for treating interstitial pneumonia, whereas steroid pulse therapy (SPT) has been prescribed for critically-ill COVID-19 pneumonia patients. [7][8][9] Three randomized controlled trials (RCTs) showed that high-dose steroid therapy improved outcomes in moderate to critically ill COVID-19 pneumonia patients. 4,5,10 However, Japanese COVID-19 guidelines include "no recommendation" for SPT, 11 based on only one low-quality RCT 5 using a nonstandard corticosteroid dose in Japan.…”
Section: Introductionmentioning
confidence: 99%